Unveiling Molecular Signatures in Light-Induced Seed Germination: Insights from PIN3, PIN7, and AUX1 in Arabidopsis thaliana - Tognacca, Rocío Soledad (2024)
Light provides seeds with information that is essential for the adjustment of their germination to the conditions that are most favorable for the successful establishment of the future seedling. The promotion of germination depends mainly on environmental factors, like temperature and light, as well as internal factors associated with the hormonal balance between gibberellins (GA) and abscisic acid (ABA), although other hormones such as auxins may act secondarily. While transcriptomic studies of light-germinating Arabidopsis thaliana seeds suggest that auxins and auxin transporters are necessary, there are still no functional studies connecting the activity of the auxin transporters in light-induced seed germination. In this study, we investigated the roles of two auxin efflux carrier (PIN3 and PIN7) proteins and one auxin influx (AUX1) carrier protein during Arabidopsis thaliana seed germination. By using next-generation sequencing (RNAseq), gene expression analyses, hormonal sensitivity assays, and the quantification of indole-3-acetic acid (IAA) levels, we assessed the functional roles of PIN3, PIN7, and AUX1 during light-induced seed germination. We showed that auxin levels are increased 24 h after a red-pulse (Rp). Additionally, we evaluated the germination responses of pin3, pin7, and aux1 mutant seeds and showed that PIN3, PIN7, and AUX1 auxin carriers are important players in the regulation of seed germination. By using gene expression analysis in water, fluridone (F), and ABA+F treated seeds, we confirmed that Rp-induced seed germination is associated with auxin transport, and ABA controls the function of PIN3, PIN7, and AUX1 during this process. Overall, our results highlight the relevant and positive role of auxin transporters in germinating the seeds of Arabidopsis thaliana.